Uzbek Language and Its Impact on Cultural and National Identity (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Language is the essence of cultural identity, reflecting a nation's historical, social, and spiritual development. This study explores the profound connection between language and national identity, focusing on the Uzbek language. By examining theoretical perspectives, historical evolution, and contemporary challenges, the research highlights the role of language in preserving cultural heritage and fostering national unity. The analysis draws on recent studies to address issues such as globalization, linguistic influence, and policy reforms aimed at promoting Uzbek as a state language. Emphasising the significance of language in shaping collective consciousness, the study underscores the importance of safeguarding linguistic traditions amidst modern transformations. The phrase "Til – millat ko'zgusi" aptly captures the Uzbek language's dual role as a cultural mirror and a dynamic tool for societal progress.